Microporous Hydroxyapatite Ceramic Composites as Tissue Engineering Scaffolds: An Experimental and Computational Study. Issue 7 (22nd March 2018) - Kanhed, Satish; Awasthi, Shikha; Midha, Swati; Nair, Jitin; Nisar, Ambreen; Patel, Anup Kumar; Pandey, Aditi; Sharma, Rajeev; Goel, Sneha; Upadhyaya, Anish; Ghosh, Sourabh; Balani, Kantesh
Abstract : Bone‐tissue engineering mandates the development of multi‐functional bioactive porous hydroxyapatite (HAp) scaffolds. Herein, microwave sintered HAp/ZnO and HAp/Ag composite scaffolds with ≈5–19% porosity are developed using 0–30 vol% graphite as a porogen. The mechanical properties of the porous scaffold are analyzed in detail, revealing that even being more porous, the reinforcement of ZnO (9% porosity, hardness of 2.8 GPa, and toughness of 3.5 MPa.m 1/2 ) has shown to have better hardness and fracture toughness when compared to Ag (5% porosity, hardness of 1.6 GPa, and toughness of 2.6 MPa.m 1/2 ). The flexural strength obtained experimentally are complemented with a finite‐element technique that adopts microstructural features in visualizing the effect of porosity on stress distribution. The antibacterial efficacy and cytocompatibility of these composites are validated by increased metabolic activity and conspicuous cell‐matrix interactions. The anticipation of the results reveal that HAp/ZnO (9% porosity) and HAp/Ag (5% porosity) composites can be used as a potential multi‐functional bone implant scaffolds. Abstract : Reinforcements of ZnO (1.33 vol%) and Ag (0.71 vol%) in porous HAp scaffolds exhibits enhanced fracture toughness via crack deflection (in ZnO), crack bridging, and plastic work (in Ag). In addition, the antibacterial efficacy and unhindered cytocompatibility substantiates the candidature of porous HAp‐Ag/ZnO composites as potential scaffolds for bone tissue replacement.